2020
DOI: 10.31661/gmj.v9i0.1711
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bone Density Reduction and Its Related Factors in Hemophilia Patients in South Khorasan Province in 2018

Abstract: Background: The present study aimed to determine the prevalence of bone density reduction and its associated factors in hemophilia patients in South Khorasan Province in 2018. Materials and Methods: This case-control study was conducted on all patients with hemophilia type A with medical records in Hemophilia center in South Khorasan province. A number of 57 eligible subjects who met the criteria were selected based on census method. Thereafter, 60 non-hemophilic individuals who were similar to hemophilic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 22 publications
(25 reference statements)
0
7
1
Order By: Relevance
“…However, a recent study came up with the opposite effect. Here, Alireza Ehsanbakhsh 17 showed that lean patients had the highest relative frequency of BMD reduction, and overweight patients had no BMD reduction, the difference being statistically significant, which is inconsistent with the results of this study. This difference may be related to the age of the subjects studied.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, a recent study came up with the opposite effect. Here, Alireza Ehsanbakhsh 17 showed that lean patients had the highest relative frequency of BMD reduction, and overweight patients had no BMD reduction, the difference being statistically significant, which is inconsistent with the results of this study. This difference may be related to the age of the subjects studied.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, according to the subjective judgement of bias risk and research quality, two of the included studies were of high quality 16,19 . NIne were of medium quality 1,17,20–26 . One was of low quality 18 ; we adjusted the studies with higher bias, the most common being age, haemophilia type, ethnicity, body mass index and number of joint diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All eligible studies were published in English. Of these included studies, 13 reported prevalence of low BMD as an outcome [ 21 – 23 , 26 35 ], and 16 reported changes in BMD as an outcome [ 17 22 , 24 28 , 30 , 31 , 33 35 ]. 16 studies [ 17 22 , 24 28 , 30 , 31 , 33 35 ] examined BMD of lumbar spine (LS), 6 [ 20 , 22 , 24 , 26 , 27 , 31 ] examined BMD of femoral neck (FN), and 6 [ 19 , 26 , 27 , 31 , 33 , 35 ] examined BMD of total hip (TH).…”
Section: Resultsmentioning
confidence: 99%